Islamic Finance and Financial Inclusion : Measuring Use of and Demand for Formal Financial Services among Muslim Adults - Demirguc-Kunt, Asli; Klapper, Leora; Randall, Douglas (World Bank, Washington, DC, 2014)
In recent years, the Islamic finance industry has attracted the attention of policy makers and international donors as a possible channel through which to expand financial inclusion, particularly among Muslim adults. Yet cross-country, demand-side data on actual usage and preference gaps in financial services between Muslims and non-Muslims have been scarce. This paper uses novel data to explore the use of and demand for formal financial services among self-identified Muslim adults. In a sample of more than 65,000 adults from 64 economies (excluding countries where less than 1 percent or more than 99 percent of the sample self-identified as Muslim), the analysis finds that Muslims are significantly less likely than non-Muslims to own a formal account or save at a formal financial institution after controlling for other individual- and country-level characteristics. But the analysis finds no evidence that Muslims are less likely than non-Muslims to report formal or informal borrowing. Finally, in an extended survey of adults in five North African and Middle Eastern countries with relatively nascent Islamic finance industries, the study finds little use of Sharia-compliant banking products, although it does find evidence of a hypothetical preference for Sharia-compliant products among a plurality of respondents despite higher costs.